Successful coaching for leaders and managers : how to blend virtual and face to face coaching effectively for today's hybrid workplaces - McCarthy, Grace (Routledge, 2025)
"The rapid pace of change in the post-COVID world has made it more important than ever for managers to coach individual employees and teams effectively both online and face to face. This book draws on research from around the world and shares good practices to help managers become effective leaders in face to face, virtual and hybrid workplaces. The book examines how the coaching skills of observation, listening, questioning, goal-setting, feedback and reflection can be used effectively with individuals and teams. Vignettes and practical activities help the reader understand how to apply these skills in real life. The book goes on to explore coaching at the organisational level, bringing in systems thinking, coaching culture, cross-cultural coaching and coaching in multi-national organisations. Finally, the book considers ways for managers to evaluate and improve their coaching including how to use technology and GenAI to support coaching. This book synthesises different strands of research to help managers develop their coaching skills both face to face and online. HR managers will find ideas for how best to support managers in developing their skills. Researchers and educators interested in managerial coaching and successful leadership in the post-COVID hybrid workplace will also find food for thought"--